The Role of Bawaslu Bekasi Regency in Law Enforcement on Violations of Election Crimes in 2024 - Wahyudi, Endik; Mardhiyyah, Chairunnisa (MIH FH UNSOED, 2024)
Simultaneous General Elections which are held every 5 (five) years create a momentum that cannot be underestimated. To achieve honest elections, election organizers with integrity are needed, election organizers consist of the KPU (General Election Commission), Bawaslu (Election Supervisory Body), and DKPP (Election Organizer Honorary Council). Bawaslu is a body formed by the government to supervise elections. The purpose of this research is to determine